Implementasi Algoritma Linear Congruentials Generator Untuk Menentukan Posisi Jabatan Kepanitiaan - Suendri Suendri (Program Studi Sistem Informasi, 2017)
Determination of the committee position an event during this time has been determined by the authorities in an organization. However, the positioning sometimes falls to the same person with the same position. This is certainly a form of injustice in the positioning. Linear Congruential Generator or LCG is one of the methods of Random Number Generator. With this Algorithm the position can be randomized so that the same person does not occupy the same position for the second time so justice can be realized.Keywords: Algorithm, Position, Organization, LCG, Justice.